NiS/Cc composite electrocatalyst as efficient Pt-free counter electrode for dye-sensitized solar cells. (1st July 2016) - Guo, Mingxing; Zhao, Fengling; Yao, Yigang; Wang, Simeng; Yin, Shuhui
Abstract: A nickel sulfide/conductive carbon composite electrocatalyst was synthesized and used as counter electrode (CE) material for dye-sensitized solar cells (DSSCs). This material demonstrates superior electrocatalytic activity in the reduction of triiodide to iodide and has a high power conversion efficiency of 8.15% compared with that of the DSSC with commercial Pt-coated CE ( η = 8.29%).